Dual‐frequency irradiation CEST‐MRI of endogenous bulk mobile proteins. (19th April 2018) - Goerke, Steffen; Breitling, Johannes; Zaiss, Moritz; Windschuh, Johannes; Kunz, Patrick; Schuenke, Patrick; Paech, Daniel; Longo, Dario L.; Klika, Karel D.; Ladd, Mark E.; Bachert, Peter
Abstract : A novel MRI contrast is proposed which enables the selective detection of endogenous bulk mobile proteins in vivo . Such a non‐invasive imaging technique may be of particular interest for many diseases associated with pathological alterations of protein expression, such as cancer and neurodegenerative disorders. Specificity to mobile proteins was achieved by the selective measurement of intramolecular spin diffusion and the removal of semi‐solid macromolecular signal components by a correction procedure. For this purpose, the approach of chemical exchange saturation transfer (CEST) was extended to a radiofrequency (RF) irradiation scheme at two different frequency offsets (dualCEST). Using protein model solutions, it was demonstrated that the dualCEST technique allows the calculation of an image contrast which is exclusively sensitive to changes in concentration, molecular size and the folding state of mobile proteins. With respect to application in humans, dualCEST overcomes the selectivity limitations at relatively low magnetic field strengths, and thus enables examinations on clinical MR scanners. The feasibility of dualCEST examinations in humans was verified by a proof‐of‐principle examination of a brain tumor patient at 3 T. With its specificity for the mobile fraction of the proteome, its comparable sensitivity to conventional water proton MRI and its applicability to clinical MR scanners, this technique represents a further step towards the non‐invasive imaging of proteomic changes in humans. Abstract : In this study, a novel chemical exchange saturation transfer (CEST)‐based technique is proposed, enabling the selective detection of endogenous bulk mobile proteins in vivo . Specificity was achieved by measurement of the coupling between different CEST signals. The feasibility of examinations in humans was verified by a first proof‐of‐principle examination of a brain tumor patient at 3 T.